Journal of African Christian Biography: v. 2, no. 4 - Amanze, James Nathaniel (Journal of African Christian biography, 2017)
A publication of the Dictionary of African Christian Biography with U.S. offices located at the Center for Global Christianity and Mission at Boston University. This issue focuses on: 1. The Martyrdom of Bernard Mizeki. 2. Bernard Mizeki. 3. Manche Masemola and Albert Luthuli: Iconic Figures of South African Christianity. 4. Manche Masemola. 5. Albert John Mvumbi Luthuli. 6. Multi-Talented Peacebuilder: Ambassador Dr. Bethuel A. Kiplagat. 7. Recent Print and Digital Resources Related to Christianity in Afric